Entrepreneurial Intentions and Career Preferences Among Malawian Vocational Students - Dwivedy, Yogesh; Gandhi, Navdeep (Journal of Educational Research and Policies, 2025)
This study investigates how entrepreneurial intentions influence career paths among technical and vocational education and training (TEVET) students, focusing on pre - training preferences, post - training aspirations, and long - term entrepreneurial ambitions. Using statistical analysis, the research evaluates factors such as pre - training entrepreneurial preferences, immediate post - training intentions, and long - term aspirations (five and ten years post - graduation) to assess their influence on career choices, particularly self - employment, wage employment, or combined paths. The research gathered primary data from 334 TEVET students and graduates at Lilongwe Technical College and DonBosco Technical Institute. The investigation was grounded in the Theory of Planned Behavior (TPB), which facilitated the examination of attitudes, subjective norms, and perceived behavior. To analyze career choices as a dependent variable through multinomial logistic regression, we assessed how perceptions of training duration, intensity, curriculum relevance, instructor expertise, level of study, college affiliation, prior training before TEVET, business ownership, involvement in a family business, gender, and field of study affect the career choices of TEVET students. The findings reveal that while a pre - training preference for entrepreneurship does not significantly predict career outcomes, a strong desire to start a business immediately after training is a significant factor. This underscores the critical role of post - training entrepreneurial momentum. Conversely, medium - term aspirations (five years) do not influence career preferences significantly, whereas long - term aspirations (ten years) emerge as a meaningful predictor, reflecting a strategic approach to entrepreneurship through resource accumulation and network building. The study also highlights a baseline preference for self - employment among TEVET graduates, independent of other variables, suggesting the presence of intrinsic motivations and an entrepreneurial orientation within TEVET programs. Respondents with strong entrepreneurial aspirations—whether immediate or long - term—are significantly more likely to prefer self - employment or mixed career paths, while those with weaker aspirations gravitate toward wage employment. These findings emphasize the importance of targeted interventions, including post - training support, mentorship, business incubation, and long - term career planning, to enhance entrepreneurial outcomes. The research underscores the need for a holistic approach to entrepreneurship education and support, addressing both intrinsic motivations and external barriers to empower TEVET graduates in their career trajectories.